Deforestation in Madre de Dios: A hell for biodiversity - Alva-Avila, Rosmel Omar (2023)
One of the most serious problems in the Peruvian Amazon is deforestation, which has its greatest expression in the region of Madre de Dios. For this reason, the objective of this article is to report on the impact caused by deforestation in Madre de Dios on biodiversity, which comprise enlightening the loss of forests due to mining and agriculture, and the diminution of mammal and bird species. A qualitative methodology has been used, for this, a systematic review was made, and existing research studies were analyzed, with which statistical data regarding the progression of deforestation in Madre de Dios from 2002-2021 and the current conservation status of mammal and bird species were finally obtained. All of the above evidence a significant increase in deforestation between 1999-2021. Likewise, a negative impact on biodiversity, specifically birds and mammals. For all these reasons, this environmental problem must be addressed, as well as the importance of developing sustainable mining and agriculture and therefore mitigate the environmental impacts generated in the Amazon.